Diagnosis and Management of Rectal Neuroendocrine Tumors - Shreya Chablaney; Zachary A. Zator; Nikhil A. Kumta (Korean Society of Gastrointestinal Endoscopy, 2017)
The incidence of rectal neuroendocrine tumors (NETs) has increased by almost ten-fold over the past 30 years. There has been a heightened awareness of the malignant potential of rectal NETs. Fortunately, many rectal NETs are discovered at earlier stages due to colon cancer screening programs. Endoscopic ultrasound is useful in assessing both residual tumor burden after retrospective diagnosis and tumor characteristics to help guide subsequent management. Current guidelines suggest endoscopic resection of rectal NETs ≤10 mm as a safe therapeutic option given their low risk of metastasis. Although a number of endoscopic interventions exist, the best technique for resection has not been identified. Endoscopic submucosal dissection (ESD) has high complete and en-bloc resection rates, but also an increased risk of complications including perforation. In addition, ESD is only performed at tertiary centers by experienced advanced endoscopists. Endoscopic mucosal resection has been shown to have variable complete resection rates, but modifications to the technique such as the addition of band ligation have improved outcomes. Prospective studies are needed to further compare the available endoscopic interventions, and to elucidate the most appropriate course of management of rectal NETs.